EFEKTIVITAS PENGGUNAAN SPESIMEN JAMUR SEBAGAI MEDIA PEMBELAJARAN TERHADAP HASIL BELAJAR BIOLOGI DI SMAS MUHAMMADIYAH KALOSI KABUPATEN ENREKANG - Noni; Asmawati Aziz, Andi; Rahmat Saleh, Andi (Universitas Cokroaminoto Palopo, 2024)
This study aims to determine the results of learning using mushroom specimens on learning outcomes in class X fungi / fungi material of SMAS Muhammadiyah Kalosi. This type of research is a quasi-experiment. Popluasi in this study were all students of class X IPA SMAS Muhammadiyah Kalosi with a research sample consisting of 2 classes, namely science 2 as the experimental group and science class 1 as the control group. Data collection techniques using test methods. The data analysis techniques carried out are descriptive statistical analysis and inferential statistical analysis consisting of prerequisite tests and hypothesis tests. The results showed that the learning outcomes of students on mushroom material using mushroom specimens (experimental class) obtained an average score of 81.68 with a good category while the learning outcomes of students who did not use mushroom specimens (control class) obtained an average score of 79.31 with a good category. And there is a significant difference in learning outcomes between the experimental class and the control class, so it can be concluded that the use of mushroom specimens is effective on the biology learning outcomes of students in class X IPA SMAS Muhammadiyah Kalosi mushroom material.